Negotiating the Paradox of Trust: A Metajournalistic Discourse Analysis of Radio Suara Surabaya - Krisdinanto, Nanang; Apul, Merlina Maria Barbara; Lapalelo, Putra Aditya (Jurnal Kajian Jurnalisme, 2026)
Background: This study is based on the emerged contradiction regarding trust in the study of journalism. Initially, trust is the main source of legitimacy which cannot be negotiated for news media. In contrast, this has caused limitations in media’s commercial operating space to sustain its organisational economics. The closest example is local media, which has been trying to strengthen the trust to maintain its legitimacy. Purpose: The purpose of this study is to analyze how actors at Suara Surabaya Radio construct and negotiate trust through metajournalistic discourse, along with its implications for journalistic legitimacy and the organization’s economic sustainability. Methods: This research used a qualitative approach, employing a discursive case study design that positions Suara Surabaya Radio as a reflective case. Primary data were obtained through focus group discussions (FGDs) involving editorial and managerial actors, and supplemented by the organization’s historical documents and previous research.  Results: For actors of Suara Surabaya Radio, trust is built through a lengthy institutional process that serves as a moral compass for conducting journalistic practices. However, trust also creates pressure from raising public expectations, devising strategies to increase revenue within monetisation limits that could lead to a breach of trust. This is where the paradox lies: media legitimacy is obtained through trust, but it does not guarantee economic gains amidst an increasingly platformised media ecosystem. Conclusion: This study introduces the concept of the “paradox of trust” to explain how trust can simultaneously serve as a source of legitimacy and a constraint on the monetization of local media. Implications: The findings of this study expand the research’s landscape on trust, showing that the sustainability of local media is also linked to the discourse on which values should be upheld and which changes are considered legitimate, and is not solely related to business and technology.